2015
DOI: 10.1038/srep15241
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of the ACOSOG Z0011 Criteria to Chinese Breast Cancer Patients: A Multicenter Study

Abstract: The aim of this study was to determine the feasibility of the Z0011 criteria to Chinese breast cancer patients. An survey about the Z0011 trial was distributed and we collected 658 consecutive patients with axillary lymph node dissection (ALND) after positive sentinel lymph node (SLN) biopsy from five centers’ databases and grouped them as eligible or ineligible for omitting ALND according to the Z0011 criteria. The eligible group was compared with the cohort included in the Z0011 trial and with the ineligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…Based on these results, American Society of Clinical Oncology Clinical Practice Guideline and National Comprehensive Cancer Network (NCCN) recommend that women who meet the Z0011 criteria may not undergo ALND 7 , 8 . Increasing number of patients undergo SLN biopsy which could avoid the underlying morbidity of ALND 9 11 .However, a subset of patients with limited disease burden on SLN may have relatively high aggressive behavior and poor survival after SLNB. Thus, it is important to explore the poor prognostic factors in breast cancers with SLNs involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, American Society of Clinical Oncology Clinical Practice Guideline and National Comprehensive Cancer Network (NCCN) recommend that women who meet the Z0011 criteria may not undergo ALND 7 , 8 . Increasing number of patients undergo SLN biopsy which could avoid the underlying morbidity of ALND 9 11 .However, a subset of patients with limited disease burden on SLN may have relatively high aggressive behavior and poor survival after SLNB. Thus, it is important to explore the poor prognostic factors in breast cancers with SLNs involvement.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the results of our pilot study regarding the Chinese patient population will have a great effect on the clinical practice of Chinese surgeons in treating patients with breast cancer. [6] 132 39% Delpech [5] 87 29% Miao Liu [15] 151 25.2% Verheuvel [19] 625 26% Ngui [7] 22 27.3% Present study 27 25.94%…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, we led a retrospective analysis and found that the clinicopathological factors were not statistically different between the eligible group in China and the Z0011 cohort. These findings laid the foundation for omitting ALND in Chinese patients according to the Z0011 criteria [15]. However, no prospective clinical trial result has been reported in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, American Society of Clinical Oncology Clinical Practice Guideline and National Comprehensive Cancer Network (NCCN) recommends that women who meet the Z0011 criteria may not undergo ALND [7,8] . Thus, increasing number of patients are omitting ALND in favor of SLNB can avoid the underlying morbidity of ALND [9][10][11] .However, a subset of patients with limited disease burden on SLN may have relatively high aggressive behavior and poor survival after SLNB. Thus, it is important to explore the poor prognostic factors in breast cancers with SLNs involvement.…”
Section: Introductionmentioning
confidence: 99%